2007
DOI: 10.1128/aac.00605-07
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silver Content on the Structure and Antibacterial Activity of Silver-Doped Phosphate-Based Glasses

Abstract: Staphylococcus aureus can cause a range of diseases, such as osteomyelitis, as well as colonize implanted medical devices. In most instances the organism forms biofilms that not only are resistant to the body's defense mechanisms but also display decreased susceptibilities to antibiotics. In the present study, we have examined the effect of increasing silver contents in phosphate-based glasses to prevent the formation of S. aureus biofilms. Silver was found to be an effective bactericidal agent against S. aure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
91
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 42 publications
5
91
0
Order By: Relevance
“…It is reported that the incorporation of silver into implants is a most promising method in reducing the infection rate, while exhibiting low toxicity towards cells and tissues [60]. Silver incorporating biomaterials, therefore, have tremendous potential for advancing the safety of internal implant therapies in the health care industry [61][62][63]. With the exception of several publications [64][65][66][67], there were no systematic studies regarding light-, heat-, chemically stable, water insoluble silver(I) antimicrobial compounds targeting specific infections, and no oxime-based compounds were tested on that matter at all.…”
Section: Agecomentioning
confidence: 99%
“…It is reported that the incorporation of silver into implants is a most promising method in reducing the infection rate, while exhibiting low toxicity towards cells and tissues [60]. Silver incorporating biomaterials, therefore, have tremendous potential for advancing the safety of internal implant therapies in the health care industry [61][62][63]. With the exception of several publications [64][65][66][67], there were no systematic studies regarding light-, heat-, chemically stable, water insoluble silver(I) antimicrobial compounds targeting specific infections, and no oxime-based compounds were tested on that matter at all.…”
Section: Agecomentioning
confidence: 99%
“…2,3 Although the antimicrobial activity of silver is well known, its mechanism of action is not yet fully understood. Several mechanisms have been proposed, such as a loss of the replication ability of DNA 4 and changes in membrane structure. 5 Carbon nanotubes (CNTs) are used in many nanocomposites, because they possess distinct mechanical and electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Biofilm-associated bacteria show decreased susceptibilities to antibiotics (4), disinfectants (13), and clearance by host defenses (7,16). Hence, the development of alternative strategies for combating biofilm-associated infections, such as the use of controlled metal ion-releasing phosphate-based glasses (PBGs), is of considerable interest (10,19). Silver cations exhibit broad antimicrobial activity at low concentrations, and they are already being used for the treatment of burn wounds (14) and traumatic injuries (3).…”
mentioning
confidence: 99%
“…Ahmed et al (1,2) have shown that PBGs containing silver in its ϩ1 oxidation state exert antibacterial effects against planktonic P. aeruginosa and S. aureus. Valappil et al (19) reported that 10, 15, and 20 mol% levels of silver in PBGs were useful in preventing the growth of S. aureus biofilms. However, striking a balance between antimicrobial and cyto-/biocompatibility is of major importance for the in vivo clinical application of these PBGs.…”
mentioning
confidence: 99%